2022
DOI: 10.1111/hsc.14110
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and prosocial behaviour in Spanish care professionals of dependent persons

Abstract: Professional residential care providers face several stressors due to the burden of caring for dependent people. This burden may affect the way in which care is carried out. Resilience, as personal strengths, may help them to be more effective in their workplace and in their interaction with patients, and this may be related to the development of participation skills and prosocial behaviours. A total of 125 professional's caregivers from Spain responded to the Connor‐Davidson Resilience Scale Resilience Scale … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Research has found that higher levels of resilience are associated with greater altruistic behavior, including volunteering and charitable donations. A study of professional's caregivers in Spain (Martí-Vilar et al, 2022) found that resilience is a variable prediction of altruistic behavior in health and social professionals. Resilience gets in the individual the capacity to be attentive to give answers in certain situations, being a predictor of great relevance of the altruistic behavior.…”
Section: Multiple Mediating Effectsmentioning
confidence: 99%
“…Research has found that higher levels of resilience are associated with greater altruistic behavior, including volunteering and charitable donations. A study of professional's caregivers in Spain (Martí-Vilar et al, 2022) found that resilience is a variable prediction of altruistic behavior in health and social professionals. Resilience gets in the individual the capacity to be attentive to give answers in certain situations, being a predictor of great relevance of the altruistic behavior.…”
Section: Multiple Mediating Effectsmentioning
confidence: 99%